Life Cycle Assessment of Maritime Pine Wood: A Portuguese Case Study - Ferreira, José (2021)
Life Cycle Assessment has become one of the most recognized and internationally accepted method for examining the environmental performance of forest products and processes. The main aim of this study was to evaluate the potential environmental impact associated with different commercial outputs of maritime pine wood (round, industrial, and residual) produced in the Portuguese forest under natural regeneration. Identifying the hotspots in the life cycle (cradle-to-gate) of each sort of maritime pine was another objective of the study. SimaPro software was used for this study, whilst the CML-IA (baseline) method was chosen to assess the environmental impacts. The study showed that round wood presented the highest values in all impact categories and industrial wood presented the lowest values except in photochemical oxidation where residual wood was the best co-product when economic allocation is chosen. The major hot spots appeared to be the felling and hauling processes due to fossil fuel combustion in the chainsaw and forwarder, respectively. The co-product that should be more environmentally friendly considerably depends on the allocation procedure chosen.